2019
DOI: 10.18502/ijhoscr.v13i3.1271
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract from Aerial Parts of Artemisia Annua L. Induces Cytotoxicity and Enhances Vincristine-Induced Anticancer Effect in Pre-B Acute Lymphoblastic Leukemia Cells

Abstract: Background: Nowadays, remarkable attention has been drawn towards the effective therapeutic characteristic of natural products targeting cancerous cells. This study aimed to investigate the anti-cancer effect of Artemisia annua extract (AAE), a Chinese herbal medicine alone and in combination with a microtubule binding agent used in ALL treatment, vincristine (VCR), in B-Acute lymphoblastic leukemia (ALL) Nalm-6 and Reh cells. Materials and Methods: Cytotoxic activity of AAE and VCR was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…for the NALM6 cell line was 1.83 nM (Figure 1C). These values are in concordance with other reports (Darvishi et al, 2017;Mashati et al, 2019) and were used in all subsequent experiments. Next, we evaluated whether exposure to BPA, BADGE, or PFOA at concentrations of 1 and 10 nM could have a protective effect against VCR-induced cytotoxicity.…”
Section: Resultssupporting
confidence: 92%
“…for the NALM6 cell line was 1.83 nM (Figure 1C). These values are in concordance with other reports (Darvishi et al, 2017;Mashati et al, 2019) and were used in all subsequent experiments. Next, we evaluated whether exposure to BPA, BADGE, or PFOA at concentrations of 1 and 10 nM could have a protective effect against VCR-induced cytotoxicity.…”
Section: Resultssupporting
confidence: 92%
“…In comparison, the standard cyclophosphamide was more toxic to these cells, with respective IC 50 values of 3.12 ± 0.13, 5.74 ± 0.20, and 6.04 ± 0.21 µg/mL. Previous studies have also shown different species of Artemisia in various cancer cells [ 47 , 48 , 49 , 50 ]. In addition, the green synthesized nanoparticles from different Artemisia species are also reported to exert antiproliferative effects on cancer cells mediated through apoptotic cell death [ 23 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 85%
“…The latter showed considerable cytotoxicity when AAE was used alone or combined with Vincristine. Thus, suggesting that using AAE in conjunction with Vincristine would allow for lower Vincristine concentrations, leading to lesser general toxicity in ALL treatment [19]. Nevertheless, more research in a clinical context could help to confirm the ALL's efficacy and assess the usefulness of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extract upregulated caspase-3 and Bax, the essential genes engaged in the apoptotic signaling, accompanied by an apparent inhibitory action on the transcriptional action of the antiapoptotic gene, Bcl-2. As a result, AAE increased Vincristine caused cytotoxic effects by modifying Bax and Bcl-2 mRNA expression [19].…”
Section: Herbs Targeting All Cell Lines Artemisia Annuamentioning
confidence: 97%